IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH (PBL) UNTUK MENDESKRIPSIKAN PEMAHAMAN DAN DAYA INGAT SISWA DALAM IPAS DI SEKOLAH DASAR - Sofi Pathul Zahra (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This research is motivated by the low understanding and memory of students on Natural and Social Sciences material in Elementary Schools. Many students have difficulty in understanding and memorizing the terms contained in the material, and lack of interest in learning and less varied learning approaches. The purpose of this study is to describe the implementation of problem-based learning models in improving students' understanding and memory of Science material. This study uses a qualitative descriptive method with interview and documentation techniques, open questionnaires, evaluation sheets. The subjects of the study were 34 fourth grade students at SDN Cibeber Mandiri 1. The results of the study showed that the application of problem-based learning models was able to increase students' learning activity, and facilitate understanding of the material, and strengthen students' memory. Thus, problem-based learning models can be an effective learning alternative to improve the quality of Science learning in Elementary Schools.